N6-methyladenosine associated prognostic model in hepatocellular carcinoma - Huang, Hanchun (Ann Transl Med, 2020)
BACKGROUND: N6-methyladenosine (m6A), the most internal mRNA modification, is involved in various cancers. However, the function of m6A in hepatocellular carcinoma (HCC) is still not well explored. Here, we aimed to develop a prognostic model consist of m6A associated genes in HCC. METHODS: The mRNA expression profiles and the corresponding clinical information from the patients with HCC were obtained from The Cancer Genome Atlas (TCGA) database, m6A differentially expressed genes (DEGs) were screened by univariate, Lasso and multivariate Cox regression analyses to develop the prognostic model. The differentially expressed m6A genes in HCC tissues were verified by quantitative reverse transcription PCR (qRT-PCR). RESULTS: The DEGs were obtained between the HCC (n=374) and normal tissues (n=50). Nine m6A genes were correlated with the prognosis, and five of them (KIAA1429, METTL3, YTHDF1, YTHDF2, ZC3H13) were included in the prognostic model by Lasso regression analyses. Four genes (KIAA1429, METTL3, YTHDF1, YTHDF2) were proved significantly high expression in our ten pairs of matched HCC and normal tissues by PCR. The HCC patients were divided into two groups (high- and low-risk) according to the risk score. The high-risk group associated with a significant poor prognosis (P=1.72×10(–4)). The time-dependent receiver operating characteristic (ROC) curve analysis confirmed the good performance of this prognostic model (AUC =0.617). After univariate [P<0.001, 1.213 (1.136−1.295)] and multivariate Cox regression analyses [P<0.001, 1.198 (1.115−1.288)] by combined with other clinical factors, this prognostic model was identified as an independent prognostic factor of HCC patients. CONCLUSIONS: The m6A genes were differentially expressed between HCC and normal tissues, and associated with the prognosis of HCC.